2: Ex-vivo Normothermic Preservation Of Amputated Limbs With A Hemoglobin-based Oxygen Carrier (HBOC-201) Perfusate. (July 2021) - Figueroa, Brian A.; Said, Sayf A.; Ordenana, Carlos X.; Rezaei, Majid; Orfahli, Lynn M.; Brunengraber, Henri; Dasarathy, Srinivasan; Papay, Francis; Rampazzo, Antonio; Bassiri Gharb, Bahar
Abstract : Background: Ex-vivo normothermic perfusion (EVNP) has been used as an alternative to static cold storage (SCS) to improve allograft quality in solid organ and vascularized composite allotransplantation (VCA). Perfusates containing red blood cells (RBCs) have shown to improve outcomes during ex vivo normothermic organ perfusion when compared to acellular perfusates. However, the use of blood products is challenging due to limited availability, the need for cross-matching, and potential blood-borne infection transmission. To avoid limitations associated with the use of blood-based products, we evaluated the feasibility of EVNLP utilizing a polymerized Hemoglobin-Based Oxygen Carrier-201 (HBOC-201). Methods: Twenty-four porcine forelimbs were procured from Yorkshire pigs following euthanasia. Six forelimbs underwent EVNLP with an HBOC-201 based perfusate, six with an RBC-based perfusate, and twelve served as static cold storage (SCS) controls. EVNLP termination criteria included systolic arterial pressure ≥115 mmHg, fullness of compartments, or tissue oxygen saturation drop by 20%. Limb contractility, weight change, compartment pressure, tissue oxygen saturation, oxygen uptake rates (OUR) were assessed. Perfusate fluid-dynamics, gases, electrolytes, metabolites, methemoglobin (MetHb), creatine kinase (CK), and myoglobin concentration were measured. Limb viability was assessed with indocyanine green (ICG) angiography, infrared thermography (IRT), and muscle histology. Results: Warm ischemia time before EVNLP was 35.50±8.62 min in HBOC-201 perfused limbs and 30.17±8.03 min in RBC-perfused limbs (p=0.07). EVNLP duration in HBOC-201 and RBC-perfused limbs was 22.5±1.7 and 28.2±7.3 hours, respectively (p=0.04). Vascular flow (325±25 vs. 444.7±50.6 ml/min; p=0.39), OUR (2.0±1.45 vs. 1.3±0.92 mlO2 /min*g of tissue; p=0.80), lactate (14.66±4.26 vs. 13.11±6.68 mmol/L; p=0.32), and perfusate pH (7.53±0.25 HBOC-201; 7.50±0.23 RBC; p=0.82) were not significantly different between treatment groups. Additionally, flexor (28.3±22.0 vs. 27.5±10.6; p=0.99) and extensor (31.5±22.9 vs. 28.8±14.5; p=0.82) compartment pressures, contractility (3±2 vs. 4±1 p=0.57), and percent weight change (23.1±3.0% vs. 13.2±22.7%; p=0.07) were not significantly different between HBOC-201 and RBC groups. In HBOC-201 perfused limbs, MetHb levels increased, reaching 47.8±12.1% at endpoint. Methemoglobin saturation did not affect OUR (ρ = -0.15, r 2 = 0.022; p=0.45). Distal tissue preservation was confirmed by IRT and ICG angiography in both EVNLP groups. Hypoxic cell clusters were identified in the SCS control group at endpoint and were absent in both treatment arms. Conclusion: HBOC-201- and RBC-based perfusates similarly support isolated limb physiology, metabolism, and function. Optimization of modifiable factors, including HBOC-201 oxidation, may extend EVNLP durations employing HBOC-201 and overcome logistical constraints of the utilization of traditional blood products.